PERANCANGAN MEDIA PEMBELAJARAN TARI TRADISIONAL KALIMANTAN TENGAH BERBASIS ANDROID - Widiatry, Widiatry (JURNAL TEKNOLOGI INFORMASI, 2019)
To advance the knowledge of people outside the world of art, especially traditional dance in Central Kalimantan requires the existence of a software technology, because at this time the delivery of information is still manual and still looking for information by visiting this traditional dance studio, so that with the Android-based learning media this is the delivery of information to be quick and easy in learning traditional dance. In this study, the stages of research are generally divided into two parts, namely (i) literature study and observation, (ii) the Waterfall model with analysis and design stages. In the analysis section the application needs are searched to determine the properties of learning media that will be created using Unfied Modeling Language (UML), namely use case diagrams, activity diagrams, and class diagrams. By designing this Android-Based Traditional Dance Learning Media it can facilitate the learning process, demonstration, and practice of learning outcomes of dances from the knowledge gained in this android system and application